Forecasting Demand for Automotive Aftermarket Inventories - Ovidiu-Alin DOBRICAN (Informatică economică, 2013)
Management decisions regarding the resource allocation in the automotive aftermarket in-volves a good understanding of it. This includes a better understanding of the participants in this market, the supply chains, specificities products and demand for these products. A useful instrument to anticipate the latter is the use of simulation methods, one of them being the Monte Carlo method, which, in this paper, is used to create various scenarios of supply.